2019
DOI: 10.3847/1538-4357/ab378e
|View full text |Cite
|
Sign up to set email alerts
|

The Red Dead Redemption Survey of Circumgalactic Gas about Massive Galaxies. I. Mass and Metallicity of the Cool Phase

Abstract: We present a search for H I in the circumgalactic medium (CGM) of 21 massive ( log M ∼ 11.4), luminous red galaxies (LRGs) at z ∼ 0.5. Using UV spectroscopy of QSO sightlines projected within 500 kpc (∼R vir ) of these galaxies, we detect H I absorption in 11/21 sightlines, including two partial Lyman limit systems and two Lyman limit systems. The covering factor of log N (H I) ≥ 16.0 gas within the virial radius of these LRGs is f c (ρ ≤ R vir ) = 0.27 +0.11 −0.10 , while for optically-thick gas (log N (−0.07… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 147 publications
(250 reference statements)
3
42
0
Order By: Relevance
“…While it can be shown that the required gas could plausibly exist in the cluster, perhaps in the form of cloudlets of ∼10 4 K photoionised gas that often envelop elliptical galaxies (e.g. Gauthier, Chen, & Tinker 2010;Thom et al 2012;Prochaska et al 2013;Farnes et al 2017;Lan & Fukugita 2017;Berg et al 2019;Pradeep et al 2019;Werner et al 2019;Liang & Remming 2020), we can test this scenario using the frequency dependence of the effect. Consider that the free-free optical depth is given by:…”
Section: Evaluation Of the Decrements And Enhancements In Source Counmentioning
confidence: 99%
“…While it can be shown that the required gas could plausibly exist in the cluster, perhaps in the form of cloudlets of ∼10 4 K photoionised gas that often envelop elliptical galaxies (e.g. Gauthier, Chen, & Tinker 2010;Thom et al 2012;Prochaska et al 2013;Farnes et al 2017;Lan & Fukugita 2017;Berg et al 2019;Pradeep et al 2019;Werner et al 2019;Liang & Remming 2020), we can test this scenario using the frequency dependence of the effect. Consider that the free-free optical depth is given by:…”
Section: Evaluation Of the Decrements And Enhancements In Source Counmentioning
confidence: 99%
“…The photoionized gas around z1 galaxies is very chemically inhomogeneous, as shown by large metallicity ranges and the large metallicity variations among kinematically distinct components in a single halo (Lehner et al 2019;Wotta et al 2019; see also Crighton et al 2013;Muzahid et al 2015Muzahid et al , 2016Rosenwasser et al 2018). Such a large metallicity variation is observed not only in the CGM of star-forming galaxies but also in the CGM of passive and massive galaxies, where there appears to be as much cold, bound H I gas as in their starforming counterparts (e.g., Thom et al 2012;Tumlinson et al 2013;Berg et al 2019;Zahedy et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cold circumgalactic medium (CGM) gas makes up a substantial fraction (30%-50%) of galactic baryons (Werk et al 2014) and may accrete onto galaxies to fuel star formation. It is then particularly intriguing that the CGMs of some quenched galaxies are observed to have massive reservoirs of cold gas (Thom et al 2012;Berg et al 2019). How these galaxies remain quenched despite these large cold gas reservoirs is uncertain.…”
Section: Introductionmentioning
confidence: 99%